2011
DOI: 10.7205/milmed-d-11-00052
|View full text |Cite
|
Sign up to set email alerts
|

Heat Strain During Explosive Ordnance Disposal

Abstract: Bomb technicians perform their work while encapsulated in explosive ordnance disposal suits. Designed primarily for safety, these suits have an unintended consequence of impairing the body's natural mechanisms for heat dissipation. Consequently, bomb technicians are known to experience symptoms of heat illness while performing their work. This research provides the first field based analysis of heat strain in bomb technicians. Six participants undertook simulated operational tasks across 2 days of variable cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 1 publication
2
31
0
Order By: Relevance
“…The Kestrel series of weather meters is widely used within environmental research, and has been shown to be effective in a wide range of environments 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The Kestrel series of weather meters is widely used within environmental research, and has been shown to be effective in a wide range of environments 18 .…”
Section: Methodsmentioning
confidence: 99%
“…This combined with a microenvironment that minimises the body’s natural capability to dissipate heat, subsequently compromises the EOD technician’s ability to maintain thermoregulatory balance. Once compromised this predisposes the EOD technician to an increased risk of heat strain and potential heat illness [2], [3]. In order to minimise this risk and the potential threat of the IED itself, EOD technicians often utilise robots to assist.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exertional heat stress is one of the most dangerous threats in the military environment, and many studies have focused on this issue [18][19][20][21][22]. Exertional heat stress leads to an increase in body temperature [23], and IRT might be an alternative method for its evaluation.…”
Section: Introductionmentioning
confidence: 99%